Simplifying the Puzzle: How Computational Thinking and Abstraction Can Help Teachers Conquer Classroom Complexity - Adeoye, Moses Adeleke; Prastikawati, Entika Fani (International Journal of Research in Education, 2024)
The investigation examines the utilization of abstraction and computational thinking by educators to effectively navigate the complexities encountered in the educational setting. It underscores the significance of these cognitive capacities in the examination and determination of intricate issues. To facilitate students in problem-solving and decision-making, educators can utilize computational thinking to break down challenging issues into more manageable components. Two capacities that educators can utilize to apply their knowledge in various circumstances are the identification of patterns and the extrapolation of abstract notions. This research study demonstrated the utility of abstraction and computational thinking in equipping educators with the necessary tools to address classroom issues, which is particularly valuable for curricula focused on training future educators. The study not only identifies potential challenges but also offers recommendations for overcoming the difficulties that teachers may encounter when implementing these ideas in the classroom. By employing these tactics and recommended solutions, educators can help students improve their analytical, problem-solving, and critical thinking abilities, thus preparing them for the challenges of the digital era.